PENGELOLAAN TUKAD BADUNG SEBAGAI OBJEK WISATA CITY TOUR DENGAN MODEL PEMBANGUNAN PARTISIPATORIS - Made Witari (JURNAL KEPARIWISATAAN, 2007)
Denpasar city government has planned Badung River as one of the tourism objects for a city tour. however, the plan has not been executed. The main problem is that the river is still very dirty and polluted by waste products. This writing explores the use of the participatory approach, an approach which involves stakeholders such as the local government, private entrepreneurs, nongoverment officers and the young generation (students) to carry out the plan.